Sonnets - Shakespeare, William; Villacañas Palomo, Beatriz (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 1994)
Sonnets XXII; CXVI; XX; XII; XCVIII; CXXXVIII; CXLIV / translated by Beatriz Villacañas Palomo